Rapid Acquisition of 14N Solid‐State NMR Spectra with Broadband Cross Polarization. Issue 48 (10th October 2013) - Harris, Kristopher J.; Veinberg, Stanislav L.; Mireault, Christopher R.; Lupulescu, Adonis; Frydman, Lucio; Schurko, Robert W.
Abstract Nitrogen is an element of utmost importance in chemistry, biology and materials science. Of its two NMR‐active isotopes, 14N and 15N, solid‐state NMR (SSNMR) experiments are rarely conducted upon the former, due to its low gyromagnetic ratio (γ) and broad powder patterns arising from first‐order quadrupolar interactions. In this work, we propose a methodology for the rapid acquisition of high quality 14N SSNMR spectra that is easy to implement, and can be used for a variety of nitrogen‐containing systems. We demonstrate that it is possible to dramatically enhance 14N NMR signals in spectra of stationary, polycrystalline samples (i.e., amino acids and active pharmaceutical ingredients) by means of broadband cross polarization (CP) from abundant nuclei (e.g., 1H). The BRoadband Adiabatic INversion Cross‐Polarization (BRAIN–CP) pulse sequence is combined with other elements for efficient acquisition of ultra‐wideline SSNMR spectra, including Wideband Uniform‐Rate Smooth‐Truncation (WURST) pulses for broadband refocusing, Carr–Purcell Meiboom–Gill (CPMG) echo trains for T2‐driven S/N enhancement, and frequency‐stepped acquisitions. The feasibility of utilizing the BRAIN–CP/WURST–CPMG sequence is tested for 14N, with special consideration given to (i) spin‐locking integer spin nuclei and maintaining adiabatic polarization transfer, and (ii) the effects of broadband polarization transfer on the overlapping satellite transition patterns. The BRAIN–CP experiments are shown to provide increases in signal‐to‐noise ranging from four to ten times and reductions of experimental times from one to two orders of magnitude compared to analogous experiments where 14N nuclei are directly excited. Furthermore, patterns acquired with this method are generally more uniform than those acquired with direct excitation methods. We also discuss the proposed method and its potential for probing a variety of chemically distinct nitrogen environments.